System of evaluation of physical preparedness of university entrants-2011 directions «Physical education» and «Health of man» - Сергієнко (Sergienko V.), Володимир Миколайович (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> 1024x768 <![endif]--> The modern system of evaluation of physical preparedness of university entrants is offered on the physical culture (creative examination) of directions «Physical education» and «Health of man». The norms of estimations are expected after a progressive scale, levels of achievements in obedience to by the 5-ball scale of sigmoid scales. Approbation practice of the given evaluation of developing motive flairs was show the proper level of preparation of candidates to the entry at higher educational establishment. <!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->